Sestamibi Positive Vs Negative Scan In Primary Hyperparathyroidism; A Clinical Dilemma (Bangladesh Journal of Nuclear Medicine, 2016)
Objectives: In primary hyperthyroidism Tc-99m Sestamibi (MIBI) scanning is commonly used for localization of abnormal parathyroid gland and the reported sensitivity is very high. However, false negative scan remain a problem. We examined whether serum calcium and parathormone (PTH) level have any impact in the sensitivity of MIBI scan.Study design: A retrospective review of 55 patients with primary hyperparathyroidism who underwent MIBI scan from January 2012 to December 2014 were included in this study. All patients underwent parathyroid surgery followed by histopathological confirmation.Results: In total, 55 patients were studied. Mean age was 41.3 ± 19.8 years (range 21-63 years). MIBI scan was true positive in 37 cases and false negative in 18 cases. The sensitivity of MIBI scan was 67.2 %. Mean serum calcium level was 12.3 mg/ dL. More than 62.2 % of patients with calcium level greater than 12.3 mg/dL had a positive scan as compared with 37.8% of those with lesser value (P